Computational thinking and tinkering: Exploration of an early childhood robotics curriculum - Bers, Marina Umaschi; Flannery, Louise; Kazakoff, Elizabeth R.; Sullivan, Amanda (Computers and education, 2014)
By engaging in construction-based robotics activities, children as young as four can play to learn a range of concepts. The TangibleK Robotics Program paired developmentally appropriate computer programming and robotics tools with a constructionist curriculum designed to engage kindergarten children in learning computational thinking, robotics, programming, and problem-solving. This paper documents three kindergarten classrooms' exposure to computer programming concepts and explores learning outcomes. Results point to strengths of the curriculum and areas where further redesign of the curriculum and technologies would be appropriate. Overall, the study demonstrates that kindergartners were both interested in and able to learn many aspects of robotics, programming, and computational thinking with the TangibleK curriculum design. •We explore the efficacy of an early childhood robotics and programming curriculum.•53 kindergarteners used developmentally appropriate robotics and programming tools.•Children's concept mastery tended to be high but varied with concept difficulty.•Results suggest effective curricular designs and areas warranting redesign.